Molecular epidemiology of Paracoccidiodes spp. recovered from patients with paracoccidioidomycosis in a teaching hospital from Minas Gerais State of Brazil - Andrade-Silva, Juliana; Andrade-Silva, Leonardo Euripedes; Paes, Hugo Costa; Alves, Lucas; Rosa, Adair; Tenório, Bernardo Guerra; Ferreira, Marcelo Simão; Felipe, Maria Sueli Soares; Teixeira, Marcus de Melo; Silva-Vergara, Mario León (PLOS Neglected Tropical Diseases, 2021)
Author summary Paracoccidioidomycosis (PCM) is one of the most important systemic mycosis of Latin America. This disease can be caused by Paracoccidioides lutzii and four different phylogenetic species: S1/Paracoccidioides brasiliensis sensu stricto that harboring S1a and S1b, PS2/Paracoccidioides americana, PS3/Paracoccidioides restrepiensis and PS4/Paracoccidioides venezuelensis. Some of these species show differences in their main geographic region of predominance such as PS2/P. americana that can be found in Venezuela and Southern Brazil; PS3/P. restrepiensis and PS4/P. venezuelensis which are distributed in Colombia and Venezuela. However, and due to their wide geographical distribution, the species S1/P. brasiliensis and P. lutzii overlapping ecological niches and can be found in different regions of Brazil and other Latin American countries. Regarding eco-epidemiological aspects, the habitat is believed to be the soil due to the predominance of the disease among rural workers who become infected by inhaling infectious propagules during their farm activities. According to other authors, these species could have relation with the different PCM clinical presentation. This study aimed to describe the molecular epidemiology associated with clinical and epidemiological data of Paracoccidiodes spp. in the Minas Gerais State, located in the Southeast region, Brazil. Among the 23 isolates herein evaluated, 22 were S1/P. brasiliensis and 1 was identified as PS2/P. americana. A total of 45 haplotypes were found when these isolates were compared with other 151 deposited in the Genbank. The preliminar finding of exclusive haplotypes according to clinical origin and geographical area would suggest correlation between the molecular profile with the clinical form and geographic origin of patients with PCM. The GP43 locus showed a higher variability and was found to be the main promotor of species differentiation. The results herein described pointed out a high intraspecific genetic variability among S1/P. brasiliensis isolates and confirm the predominance of this species in the Southeast region of Brazil.